Pre-Existing Humoral Immunity Enhances Epicutaneously-Administered Allergen Capture by Skin DC and Their Migration to Local Lymph Nodes - Hervé, Pierre-Louis; Plaquet, Camille; Assoun, Noémie; Oreal, Nathalie; Gaulme, Laetitia; Perrin, Audrey; Bouzereau, Adeline; Dhelft, Véronique; Labernardière, Jean-Louis; Mondoulet, Lucie; Sampson, Hugh A. (Frontiers in Immunology, 2021)
Due to its richness in antigen presenting cells, e.g., dendritic cells (DC), the skin has been identified as a promising route for immunotherapy and vaccination. Several years ago, a skin delivery system was developed based on epicutaneous patches allowing the administration of antigen through intact skin. Using mouse models, we have shown that epicutaneous allergen application leads to a rapid uptake and transport of allergen-positive cells to skin-draining lymph nodes (LN). This occurred primarily in animals previously sensitized to the same allergen. In that context, we sought to better understand the role of the specific preexisting immunity in allergen capture by skin DC and their subsequent migration to LN. Specifically, we investigated the role of humoral immunity induced by sensitization and the involvement of IgG Fc receptors (FcγR). Epicutaneous patches containing fluorescently-labeled ovalbumin (OVA) were applied to naïve mice that had previously received either sera or purified IgG isolated from OVA-sensitized mice. To investigate the involvement of FcγR, animals received 2.4G2 (anti-FcγRII/RIII) blocking antibody, 24 hours before patch application. Mice that received sera or purified IgG originating from OVA-sensitized mice showed an increase in the quantity of OVA-positive DC in skin and LN. Moreover, the blockade of FcγR reduced the number of OVA-positive DC in LN to a level similar to that observed in naïve animals. Overall, these results demonstrate that preexisting specific-IgG antibodies are involved in allergen capture by skin DC following EPIT through the involvement of antigen-specific IgG-FcγR.